Exploring the Interplay of Leadership, Work Environment, and Teacher Performance: Insights from Madrasah Aliyah in Soppeng Regency - NURAHMI; MUS, Abdul Rahman; SEMMAILA, Baharuddin; HAKIM, Ahmad; AHRI, Reza Aril (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The current era of globalization is characterized by very sharp and tight competition, where every organization tries and competes in competition to achieve the best, by organizing all existing systems so that they can play their proper role. Research Objectives: 1. to analyze the influence of leadership and Work Environment on the job satisfaction of Madrasah Aliyah teachers in Soppeng district 2. To analyze the influence of leadership and environment on the work performance of Madrasah Aliyah teachers in Soppeng district 3. To analyze the influence of job satisfaction on the work performance of Madrasah Aliyah teachers in Soppeng district. Quantitative research approach. The population was 211 madrasa teachers and the sample was 138 madrasa teachers. The data collection method uses a questionnaire. The sample collection method is by percentage sampling. The analysis method uses Multiple Linear Regression. The results of the research show that: (1) leadership and the work environment have a joint effect on the job satisfaction of Madrasah Aliyah teachers in Soppeng district 2. Leadership and the work environment have a joint effect on the performance of Madrasah Aliyah teachers in Soppeng district 3. Partially, leadership has no significant effect on job satisfaction of Madrasah Aliyah teachers in Soppeng district 4. Partially leadership has no significant effect on the work performance of Madrasah Aliyah teachers in Soppeng district 5. Job satisfaction has an effect on the performance of Madrasah Aliyah teachers in Soppeng district.